Umetnost kot kritika jezika - Kogler, Susanne (Muzikološki zbornik, 2007)
That art functions as a corrective to rational-scientific insights is one of the formative thoughts of art philosophy. The fact that artistic expression represents a corrective to linguistically-rationally affected insight also ranks among the constants of art philosophy in the 20th century. "Expression is the opponent of articulating something" can be read, for instance, in Adorno's Aesthetic Theory with regards to the character of language in art and Jean François Lyotard wrote on aesthetic experience: "What happens to us is by no means something which we would have controlled, programmed or conceptually apprehended beforehand". The uneducible, conceptually unattainable is also at the centre of current art production of the 21st century. On the basis of Lyotard's and Adorno's positions, the article shows that one should acknowledge a constancy of the topos of art as non-conceptual knowledge on the one hand as the continuing function of a tradition defined from the philosophical aesthetics of modernity to post-modernity and orientated on the artistic avant-garde. On the other hand and beyond this a continuous line of tradition of New Music becomes clear, leading to the expressionistic avant-garde of the 20th century which represented the starting point for Adorno's music philosophy, through Lyotard's focus on John Cage, up to the avant-garde of New Music in the era of post modernity. Specific features of contemporary art, such as rebellion against linguistic standards, an understanding of expressivity that opposes the traditional language of music and operates on the verge of silence, as well as the utopian vision of a modified reality which aims at transcendency enable a conception of art as non-conceptual knowledge, corresponding with the positions of art philosophy in modernity and post-modernity in important points. The relevance of focusing on this line of tradition for musicology lies in the fact that it sheds new light on the musical avant-garde and its further function and, last but not least, that it opens new perspectives in understanding contemporary artistic productions.
Keywords: Adorno, Theodor W., 1903-1969; aesthetics; art; avantgarda; estetika; filozofija; glasba; Lachenmann, Helmut, 1935-; Lyotard, Jean-François, 1924-1998; music; Neuwirth, Olga, 1968-; Pauset, Brice, 1965-; philosophy; umetnost